PDO certification: a brand identity for wine tourism in Catalonia (Spain) - Molleví, Gemma; Nicolas-Sans, Ruben; Álvarez, Jesús; Villoro, Jordi (Geographicalia, 2020)
The aim of this study is to analyse how PDO certification (Protected Designation of Origin) is being used to develop oenological tourism in rural areas in the Autonomous Community of Catalonia (Spain). We will also consider how marketing technologies can be applied to increment the value of the wine landscape, society and economy in rural and inland areas. A search for bibliographic information and field work was carried out in four specific regions. The results obtained are: the confirmation of the increase in the creation of oenological routes in PDO regions; the diversification of places and monuments linked to the sector of the wine that originate new tourist products; the increase of the purchasing power of the inhabitants of the rural area to have income from other economic sectors; and, the value of the PDO brand to promote a product, a territory, a culture in an agrarian society.